Gen Z Fashion on TikTok: Navigating Identity Perceptions and Revisiting Simmel’s Paradoxical Fashion Theory - Todorova, Monika (Auckland University of Technology, 2025)
Social media applications such as TikTok have created a new context for how fashion through content is engaged with and consumed, which in turn impacts and has a significant role on its users. Barnard (1996) argued that fashion is a form of communication, with meaning being embedded within a broader sociocultural environment. With this, there is opportunity to extend this notion within the updated online context of TikTok, analysing how users of TikTok platform create meaning either by consuming or uploading fashion content. This study also analyses the application’s role and impact on its user’s fashion decision-making choices and even their own perceptions of their identity. Additionally, this study explores the relevance of Simmel’s (1957) dualistic paradigm, considering the ongoing tension inherent between individuality and collectivism within the context of TikTok. To address these two research problems, the study utilised a qualitative research approach that was interpretive and phenomenological in nature. In-depth semi-structured interviews were conducted with highly fashion-conscious TikTok users within the Generation Z demographic, considered typical users of the application. Reflexive thematic analysis (Braun & Clarke, 2022) was employed, revealing different tensions surrounding the role and function of influence, critical perspectives on the algorithm and the complexities of identity representation on the app. In turn, the study found that users simultaneously criticised and found selective merit in terms of being influenced by fashion content on TikTok, showcasing high levels of discernment and weariness of the commercial or consumer-driven functions of TikTok. Meaning is revealed as participants critically monitor the fashion decision making of other people, which in turn influences their own fashion choices. The findings reveal that users are highly discerning, valuing authenticity from the content they observe and its creators. In line with Simmel’s dualistic theory, participants valued individuality in contrast to following trends, with the behaviours described by participants potentially intensifying the tension between individuality and collectivism. This study contributes new insights on the usage behaviours, critical thinking processes and how Generation Z users discern influence. Furthermore, the importance of authenticity within content and fashion are highlighted, extending understanding of social media that can be insightful to the wider community of people invested in fashion. Additionally, this study is beneficial for like minded fashion-conscious users within the cohort, as the findings can further advance understanding of their world and what is important.